Prevention and control of schistosomiasis in the Philippines from a health education perspective - Yao, Xiaodong; Chen, Yihan; Chen, Keda; Lin, Lijun; Zhong, Jiangyue; Shan, Chaojun; Liu, Mingcheng; Chen, Xintong; Zhang, Yijie; Li, Hongyu (Frontiers in Public Health, 2025)
Schistosomiasis, second only to malaria, poses a significant threat to many regions worldwide, particularly tropical and subtropical areas. The Philippines, located in a tropical region, has long suffered from the serious public health hazards of schistosomiasis. We recognize that, besides direct snail control and mass drug administration, education plays a crucial role, either directly or indirectly, in the prevention and control of schistosomiasis. Therefore, this paper delves into the current status of schistosomiasis in the Philippines, the evolving strategies for prevention and control, and the significance of these efforts, with a particular focus on analyzing the impact, achievements, and challenges of educational interventions in schistosomiasis control. This detailed analysis aims to provide a comprehensive perspective on the overall progress and challenges of schistosomiasis prevention and control in the Philippines.